2021
DOI: 10.1038/s41598-021-89678-3
|View full text |Cite
|
Sign up to set email alerts
|

Lung function decline is associated with serum uric acid in Korean health screening individuals

Abstract: We performed a retrospective cohort study of 19,237 individuals who underwent at least three health screenings with follow-up periods of over 5 years to find a routinely checked serum marker that predicts lung function decline. Using linear regression models to analyze associations between the rate of decline in the forced expiratory volume in 1 s (FEV1) and the level of 10 serum markers (calcium, phosphorus, uric acid, total cholesterol, total protein, total bilirubin, alkaline phosphatase, aspartate aminotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
3
1
Order By: Relevance
“…Open access linear mixed models. 43 Nevertheless, our study was inconsistent with another Korean study, which demonstrated there was a significant positive relationship between SUA and lung function parameters, among 69 928 participants recruited from Kangbuk Samsung Hospital Health Screening Center, Seoul, Korea. 44 The Korean study excluded the participants with a self-reported history of underlying diseases, including hypertension history, diabetes history, respiratory diseases history and so on.…”
Section: Discussioncontrasting
confidence: 97%
“…Open access linear mixed models. 43 Nevertheless, our study was inconsistent with another Korean study, which demonstrated there was a significant positive relationship between SUA and lung function parameters, among 69 928 participants recruited from Kangbuk Samsung Hospital Health Screening Center, Seoul, Korea. 44 The Korean study excluded the participants with a self-reported history of underlying diseases, including hypertension history, diabetes history, respiratory diseases history and so on.…”
Section: Discussioncontrasting
confidence: 97%
“…Another study conducted in Japan, 13 involving 2917 participants, reported that the predicted values of FEV1% and FVC% in females were inversely associated with UA. A final study from Korea 22 was conducted, a retrospective cohort analysis comprising 19 237 individuals who underwent at least three health screenings and were followed up for over 5 years. The study utilized linear mixed models to observe an accelerated decline in FVC and the FEV1/FVC ratio among non‐smokers with elevated serum UA levels.…”
Section: Discussionmentioning
confidence: 99%
“…A study using an experimental model of ILD demonstrated that bleomycin-induced lung injury triggers local production of UA, thereby activating the NALP3 inflammasome in the lung and perpetuating lung damage [ 28 ]. In addition, higher SUA and BALF-UA levels have been associated with worse pulmonary function at spirometry not only in RA-ILD but also in healthy subjects [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%